A Framework for Linking Culture and Improvement Initiatives in Organizations - Detert, James R.; Schroeder, Roger G.; Mauriel, John J. (Academy of Management Review, 2000)
James R. Detert, Roger G. Schroeder, John J. Mauriel, A Framework for Linking Culture and Improvement Initiatives in Organizations, The Academy of Management Review, Vol. 25, No. 4 (Oct., 2000), pp. 850-863